Navigating the future: Strategies for the long-term governance of socio-technical change - Stefania Sardo; Sophie Kuppler; Dirk Scheer (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2025)
Long-term governance (LTG) addresses complex, enduring socio-technical challenges such as climate change and nuclear waste management. It requires framework conditions that go beyond short-term political cycles and promote a culture of foresight and collective stewardship. In an analytical framework developed for LTG, four key elements are identified: reflexivity, anticipation, adaptation, and deliberation. Contributions to this Special topic provide insights into LTG approaches in different contexts, highlighting participatory mechanisms for democratic accountability and ethical decision making. The articles explore the complexity of LTG and the tension between long-term objectives and immediate political pressures, thus contributing to the advancement of LTG theory and knowledge base.